Otimização da ativação com carbonato de lítio (Li2CO3) através de diferentes métodos na reologia da argila verde lodo purificada para fluidos de perfuração base água e base óleo. - Brasileiro, Camila Tavares (2018)
Bentonite clays from the municipality of Boa Vista - PB have a high percentage of contaminants or coarse fractions, providing unsatisfactory rheological results for application in drilling fluids of oil wells. A purification process is necessary in order to improve the rheological behavior of these dispersions and to adapt them to the standards required by Petrobrás EP-1EP-00011-A, 2011 and API 13A, 1993.The properties of the drilling fluids as the cost of it are of extreme importance to the successful completion of an oil well. Specifically, the cations have a direct influence on the rheological behavior of these fluids. Li+ is in the first place in the selectivity plane of these cations. It has already been studied that Li2CO3, although having a high cost, presents extremely satisfactory rheological results for the application desired here. However, a more in-depth study on the improvement that this carbonate causes in all rheological properties becomes necessary. The aim of this research is to study the optimization of a bentonite clay activation from Paraíba (Verde Lodo) by different methods, as well as to evaluate the influence of lithium content on the rheological properties of aqueous and non-aqueous fluids. To this end, in addition to the traditional method (Padua) of additivation, this work, in an unprecedented way, analyzes three other methods (hot, cold and aged at 40ºC), with the aim of reducing curing time, thus optimizing the cost and production on the industrial scale. First the samples were characterized by XRD, XRF, SEM, CEC, LALLS and TGA / DTA. Then, the study was divided into two parts, where in part I was carried out the study of the rheological behavior of the purified and additive samples for water based drilling fluids.After this process, the samples were organophilized and again characterized by XRD and TGA / DTA. In part II, the apparent viscosity was studied in order to verify the compatibility in forming dispersions for nonaqueous drilling fluids based on Petrobrás standard EP-1EP-00023-A, 2011, and the flow curves were analyzed. In order to guarantee the robustness of the tests of this work, a statistical analysis was carried out, in order to evaluate the influence of the lithium content, besides the method of additivation. From the results, it was possible to infer that the traditional method can easily be replaced by the aged at 40ºC, since the statistical results show a very strong correlation of 97% between them, at a level of significance of 95% (α=5%).